Gavage ethanol induced oxidative stress and cytokine response in rat iymhoid organs - İnce, Erdal and Akyol, Sibel and Ulutin, Turgut and Tunalı, Halil (Cerrahpaşa Medical Journal, 2019)
Objectives: The purpose of the study was to investigate the relationship between ethanol, oxidative stress, the protective capacity of the antioxidant defense system and TH1 [Tümör Necrosis alpha (TNF-α), Interleukine-2 (IL-2), Interferon gamma (IFN-γ)] cytokine response in lymphoid organs such as the spleen, thymus, lymph nodes and also liver of rats. Methods: Fourty wistar rat were included in the study. Four groups included control and treated with gavage ethanol 15 d and 30 d respectively. For measurement of oxidative stress in the lymphoid tissues were determined using lipid peroxidation and protein oxidation, intracellular antioxidant status were assayed glutathione (GSH) levels and glutathione peroxidase (GP), glutathione reductase (GR), glutathione S transferase (GST), catalase (CAT), superoxide dismutase (SOD) activity and TH1 cytokine responses were assayed TNF-α, IL-2, IFN-γ levels. Results: In lymphoid tissues and liver of 10-30 d old offsprings of gavage ethanol-administrated pregnant rats, levels of lipid peroxidation and protein oxidation were established a significant increased and in intracellular antioxidant capacity markedly decrased levels of GSH, GP, GR, CAT, SOD and GST activities were increased in all tissues. In TH1 responses, TNF-α levels were increased but IFN-γ levels were decreased in both of groups. IL-2 levels were decreased in 10 day offsprings. No change in IL-2 levels were found in 30 day offspring. Conclusion: Ethanol metabolism causes oxidative stress not only in liver but also in lymhoid organs. Oxidative stress produced by the toxic injury plays an important role in this response through up-regulation of inflammatory cytokines.